Estudo da associação entre parâmetros bióticos e abióticos e a ocorrência de florações de cianobactérias no reservatório de Vargem das Flores - MG - Lenora Nunes Ludolf Gomes (2008)
The aim of this study is to understand the associations between physical, chemical and biological features and the occurrence of cyanobacteria in the water supply reservoir Vargem das Flores/MG. A monitoring program was undertaken in four sampling sites from October2004 to October 2007 to investigate the following parameters: temperature, dissolved oxygen, N-NH4 +, N-NO3 -, P-PO43-, P-TP turbidity, color, alkalinity, chlorides, conductivity, pH, totaliron, total suspended solids, phytoplankton and zooplankton quantification, chlorophyll-a, together with a molecular biology research of the cyanobacteria isolated from the reservoir. According to the results of the physical, chemical and biological factors the water column profiles presented different behavior for each sampling site. The cluster analyses found better water quality for sampling site 1, located close to the water treatment plant withdrawal. In general, the lake was stratified during the summer (raining season) leading to the formation of an anoxic hypolimnion and higher concentrations of nutrients. Deep mixing occurred only once during the cool, dry season. The cyanobacteria group followed a seasonal pattern during the three year research period. The group was absent in the dry period, returning after the onset of stratification (warm season). A succession pattern was observed within the cyanobacteria group in the reservoir. The Aphanocapsa genus (picoplankton) was dominant in the last period. The PCA analysis showed negative correlation between cyanobacteria and orthophosphate and total phosphorus concentrations. A higher concentration of phosphorus was observed just before the occurrence of cyanobacteria. The results of the molecular biology study indicated that the cyanobacterial isolates possessed only part of the genes fromthe microcystin gene cluster and only one of the isolates presented toxicity effect by protein phosphatase 2A inhibition assay, although no microcystin could be detected.